Detecting Selfish node in MANET- A Review - kaur, Jagmeet; singh, Prabhjit (International Journal of Computer Sciences and Engineering, 2025)
MANET (Mobile Ad-Hoc Network) is self-directed and infrastructure less network. MANETs contains mobile nodes that are free to move in the network. Nodes can be the devices like mobile phones, PDA, MP3 players and personal computers which are participating in network. MANET has the dynamic topology due to the node movement. Transmissions of the packet between the mobile devices are overcome by the Routing Protocol. Selfish node is a major problem in MANET. Selfish nodes are nodes that do not participate in forwarding process. This paper presents types of MANET protocols along with security issues that MANET faces. The major consideration of this paper is about the behavior and detection methods of selfish node in MANET.